Effects of Ozone Oxidation Process on Residual Antibiotics and Antibiotic Resistance Genes in a Swine Wastewater Treatment Plant - Taeyoung Cha; Min-Sang Kim; Yuhoon Hwang; Eun Sook Jeong; Hongmok Jo; Si-Kyung Cho (Applied Sciences)
Extensive antibiotic use in swine production contaminates manure and wastewater with antibiotics. Discharging this waste into the environment, even after treatment, potentially fuels the spread of antibiotic resistance. This study investigated a full-scale swine wastewater treatment plant that combines coagulation–sedimentation, sand filtration, ozonation, activated carbon filtration, and a deaeration process. At each stage of this process, samples were collected and analyzed to determine their water quality parameters, antibiotic concentrations, and antibiotic resistance genes (ARGs). The experimental results showed coagulation–sedimentation effectively removed suspended solids (92.2%) and total phosphorus (96.9%). Ozonation significantly reduced antibiotic levels, including sulfamethazine by over 99.9%, although ARGs such as tetM, sul1, and sul2 were only removed at levels up to 95.9%. Interestingly, partial rebounds of sulfamethazine (438.9 μg/L) and marbofloxacin (0.40 μg/L) appeared in the final effluent, suggesting that desorption or operational factors (e.g., hydraulic fluctuation, filter media saturation, and pH) may affect the treatment process. In addition, strong correlations emerged between the levels of suspended solids and those of certain antibiotics (lincomycin, tiamulin), indicating particle-mediated sorption as a key mechanism. Even though ozonation and coagulation–sedimentation were found to contribute to the substantial removal of pollutants, the observed rebounds and residual ARGs highlight the need for optimized operational strategies and multi-barrier approaches to fully mitigate antibiotic contamination and inhibit the proliferation of resistant bacteria in swine wastewater.